Universal Remote Controlled Lamp Dimmer / Mohd Khairul Abd Samat and Muhamad Syahir Muhamad Nazir - Abd Samat, Mohd Khairul; Muhamad Nazir, Muhamad Syahir (2004)
“UNIVERSAL REMOTE CONTROLLED LAMP DIMMER” is a home remote controlling system to control the brightness of any standard 1 10VAC incandescent lamp (up to 300W). Many household items are now supplied with remote control handsets. Single channel remote control dimmers like this are designed to control the brightness for special purposes. The prototype was used as a stand-alone system, connected to table lamps and a desk fan or elsewhere. Ambitious constructors could consider incorporating the unit into the household wiring, if they are satisfied that the installation will comply with the relevant wiring regulations